2023
DOI: 10.1109/tro.2022.3207619
|View full text |Cite
|
Sign up to set email alerts
|

Object Detection Using Sim2Real Domain Randomization for Robotic Applications

Abstract: Robots working in unstructured environments must be capable of sensing and interpreting their surroundings. One of the main obstacles of deep-learning-based models in the field of robotics is the lack of domain-specific labeled data for different industrial applications. In this article, we propose a sim2real transfer learning method based on domain randomization for object detection with which labeled synthetic datasets of arbitrary size and object types can be automatically generated. Subsequently, a state-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In this approach, a model trained predominantly on synthetic data is enhanced by incorporating a subset of real-world data during its training phase. Multiple studies have demonstrated that adding a relatively small set of real training images into a largely synthetic data set can significantly improve the models ability to generalize in the target domain (Horváth et al, 2023;Tremblay et al, 2018). However, using realistic renderings to handle the domain gap is also investigated in literature (Denninger et al, 2019).…”
Section: Domain Randomization and Domain Adaptationmentioning
confidence: 99%
“…In this approach, a model trained predominantly on synthetic data is enhanced by incorporating a subset of real-world data during its training phase. Multiple studies have demonstrated that adding a relatively small set of real training images into a largely synthetic data set can significantly improve the models ability to generalize in the target domain (Horváth et al, 2023;Tremblay et al, 2018). However, using realistic renderings to handle the domain gap is also investigated in literature (Denninger et al, 2019).…”
Section: Domain Randomization and Domain Adaptationmentioning
confidence: 99%
“…and hope that the randomization captures the distribution of the real-world data. This technique has been applied to object detection and grasping [2,18,21,47,49], and pose estimation [26,28,29,34,36,46,50,56]. The randomization is usually tuned empirically hence it is not efficient.…”
Section: Domain Adaptation For Sim-to-real Transfermentioning
confidence: 99%
“…However, the availability of labeled training data remains a major challenge as the process of data labeling is labor-intensive and costlier [9]. To overcome this, many solutions have used simulations for auto-generating the training data [4], [10] followed by sim-to-real transfer of the learning for real-world deployment [11]. Previously, It was believed that real-world visuals differ significantly from the simulated world and hence the sim-to-real transfer is not promising in the case of models trained with only synthetic RGB data [12], [13].…”
Section: Rgb-d Cameramentioning
confidence: 99%